TANGGAP KEBAL VAKSIN HEPATITIS B PADA BAYI BERAT LAHIR RENDAH DAN BAYI BERAT LAHIR NORMAL SETELAH VAKSINASI DASAR HEPATITIS B - , Muhardison ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Hepatitis B is a common disease in the world as a major cause of morbidity and mortality. Over 2 billion people are infection to the HB, 378 million carriers of HB, mortality rate 1-2 million and over 4 million acute clinical cases occur each year. Prevalence of HB in Indonesia 3-20%. Vertical and horizontal transmission in infants and children occurs 25-45%. 25-50% of children infected before 5 years. The most effective approach to reducing the burden of HB infection is primary preventive mass vaccination of new borns and children continuously. Objective: To determine immune response of HB vaccine LBW and NBW after basis HB vaccination, and factors related to the immune response to gender, pregnant age and weight gain the first 6 months of life. Methods: This retrospective cohort study. Population babies born in May-July 2012. Selected samples 106 infants aged 13-15 months after vaccination of HB recombinant basic of 4 doses of 0, 2, 3, and 4 months according to inclusion and exclusion criteria. Serum of children examined for knows anti-HBs antibody titers with Elisa method. Results are categorized respon negatif titers anti-HBs <10 IU/L and respon positif titers anti-HBs â¥10 IU/L. Hypothesis testing is used fisherâs exact and logistic regression. Results: A total of 98 subjects (92,5%) completed the study. Immune response LBW (89,7%) together with NBW (95,9%) RR 2.5 CI (0,50 to 12,2) p=0,2178. Gender was not related to immune response RR 0,6 CI (0,15 to 2,69) p=0,6996. Gestational age associated with immune response RR 8 CI (1,05 to 63,9) p=0,0399. The first 6 months weight was not related to immune response RR 3,6 CI (0,73 to 17,7) p=0.1178. Results of logistic regression LBW was not related the immune response OR 1 CI (0,16 to 7,17) p=0,929. Gestational age related to immune response OR 9 CI (1,05 to 79,3) p=0,044 and the first 6 months of weight was not related immune response OR 3,7 CI (0,65 to 21,1) p=0.138. Conclusion: Immune response of hepatitis B vaccine LBW egual than NBW. Gestational age related to immune response and weight first 6 months was not related to immune response. It is recommended to mothers have low birth weight babies do not need to worry because the immune response that is formed can protect children from the risk of infection with HB. Further research is needed that focuses on infants born preterm gestational age <37 weeks or premature immune response after basis vaccination HB.